Technological limitations of cattle breeding in La Pampa, Argentina: diagnosis and challenges (Perspectivas de las Ciencias Económicas y Jurídicas, 2025)
Livestock farming in La Pampa faces various technological restrictions that affect the productivity and competitiveness of the sector. The objective of this work is to identify and analyze the main technological limitations according to the scale of production and the region, in order to propose specific intervention strategies. The results reveal that, although there are common challenges, such as forage management and access to water, the importance of these limitations varies according to the size of the establishment and the region. Small producers mainly face problems in forage management, while on medium and large scales other challenges emerge such as the implementation of the health plan and the improvement of infrastructure and business management. The heterogeneous distribution of these limitations throughout the different regions of La Pampa, with forage management as a central priority in most areas and water availability as the most urgent problem in the West.
Keywords: innovation; competitiveness; sustainability; livestock; productivity